Integrating business model for sustainability and performance management to promote occupational health and safety—A discussion of value - Johanson, Ulf; Aboagye, Emmanuel; Yao, Jun (Frontiers in Sustainability, 2022)
The concept business model has been around in scientific discussions for over half a century, but the adaption business model for sustainability is much more recent. However, what constitutes the latter is far from clear and the concept would gain from further elaboration. For example, the concept of value necessitates further discussion in the literature addressing business models for sustainability. Furthermore, the current article emphasizes conceptual challenges pertaining to the interplay between the business model for sustainability and the internal performance management system. We argue that if the performance management system is decoupled from the business model, the long-term and short-term occupational health and safety (Bräunig and Kohstall) advantages and the sustainable value propositions to stakeholders will not be realized. OHS is a basic cornerstone in doing business and should not be viewed as an afterthought to production and financial concerns. Therefore, OHS and employee relations should be addressed within the business model. The most important issue is the alignment of the value propositions, value creation and value capture that underpin both the business model and the internal performance management system.